6 - Radical Regionalism: Feminism, Sovereignty and the Pan-African Project - Salem, Sara (Africa Development, 2022)
This article analyses how sovereignty in Africa’s immediate post-independence period was necessarily conceptualised as a regional pan-African and internationalist project of decolonisation, outlining lessons for the contemporary period. The capacity of newly independent states to shape their domestic policy and mobilise resources was constrained by their subordinate place in the global political and economic order, which made them dependent on foreign capital and tied them to the interests of their former colonisers. As such, they fostered radical regional and international solidarity that would facilitate the continent’s development. Looking at a series of feminist conferences in the immediate post-independence era, the article also traces the contributions of Southern feminists to the decolonisation project and African feminists to the conception of pan-Africanism, breaking with Western feminists to conceptualise national liberation as fundamental to gender justice.